Detecting of Biofilm Formation and Associated Genes, and Assessing PilA Gene Expression in Different Pseudomonas aeruginosa Wounds and Burns Isolated in Baghdad Hospitals - Obaid, Wisam Jawad; Ali-Nizam, Adnan Ahmad; Diwan , Zahraa Jabbar; Hussein Jabbar, Maryam Abdul; Mohhammed , Saja; A.Slman, Tabark; Fadhe, Asmaa Gahlib; Adnan, Ali Adil (Journal of Neonatal Surgery, 2025)
A total of 103 clinical specimens were obtained from patients have burns, and wounds at ages between 10 - 60 years from both genders in three hospitals in Baghdad – Iraq: Al Yarmouk Teaching Hospital, Baghdad Teaching Hospital, and Al-Karkh General Hospital and at the period from (23/9/2022 to 29/12/2022). Pseudomonas aeruginosa was isolated and identified, which showed that from a total of 130 specimens, only 103 isolates (71.87%) belonged to P. aeruginosa. The isolation rate was higher from burn infections followed by wound infections, at ratios 40.62%, and 23.75%, respectively, the rest 27 isolates (16.87%) were related to other bacterial spp. like Escherichia coli, Klebsiella pneumonia, Proteus mirabilis, Staphylococcus aureus and Enterobacter cloacae. The results showed that all P. aeruginosa isolates were a multidrug resistance to many antibiotics. Estimating the growth for isolates at different time (6, 12, 18, 24, and 36) hrs. revealed that a high OD value was detected between 18-24 hrs. The results of the molecular study to detect biofilm associated genes pil A, Psl A, Psl B, RHII and rhIAB revealed that these genes were detected in P. aeruginosa isolates at ratio (93%, 80%, 90%, 90%, and 86.6%) respectively. Also, the detection of gene expression for PilA gene in three P. aeruginosa isolates at different time 6, 12, 18, 24, and 36 hrs. by RT-PCR revealed that a high gene expression of pilA gene in P. aeruginosa isolates detected between 18-24 hrs.